411 Treatment Results of Arteriovenous Fistulas at the Craniocervical Junction: A Multicenter Cohort Study of 108 Patients. (1st April 2022) - Endo, Toshiki; Takai, Keisuke; Inoue, Tomoo; Seki, Toshitaka
Abstract : INTRODUCTION: No standard treatment has been established for the arteriovenous fistulas (AVFs) at the craniocervical junction (CCJ). METHODS: A total of 103 consecutive patients with the CCJ AVFs were collected from 29 centers that are members of Neurospinal society of Japan. Angiographic findings and the clinical characteristics of the CCJ AVFs were evaluated. RESULTS: Among 103 cases, dural AVF (59 cases), radicular AVF (12 cases), epidural AVF (16 cases), and perimedullary AVF (5 cases) were included. There were 11 cases in which combinations of the pathologies occurred in one case. 51 and 7 patients presented with subarachnoid hemorrhage (SAH) and intramedullary hemorrhage, respectively. 28 cases presented with congestive myelopathy, while there were 17 asymptomatic cases. Overall, 78 cases (76%) and 19 cases (18 %) underwent primary surgical or endovascular treatments, respectively. 4 cases (4%) underwent combined treatments. 14 cases (14%) required second treatments. The rate of initial treatment failure or recurrence was 2.6% after the surgical treatments (Surgery Group), while it was 63% of the endovascular treatment group (Endovascular Group). In multivariate analysis, endovascular treatment was the independent risk factor with significantly higher odds of initial treatment failure or recurrence (odds ratio [OR], 59; 95% confidence interval [CI], 11-324). Treatments related complications occurred in 28 cases (27 %). The rates of complications were 21% in the Surgery Group. While, it was 42% in the Endovascular Group. Complications included medulla/spinal/cerebellar infarction (12 cases), the cerebrospinal fluid leak (3 cases), and postoperative hematomas (3 cases).Post-operatively, an improvement of 1 or more in modified Rankin Scale (mRS), was observed in 60% and 37% of Surgery and Endovascular Groups, respectively with a median follow-up of 23.0 months. CONCLUSION: Based on the largest and latest multicenter cohort, this study showed that primary microsurgery was superior to endovascular treatment to achieve complete obliteration of the CCJ AVF in a single procedure.